Учреждение и развитие византийской фемы в Таврике - Науменко, В. Е. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryNaumenko V. E. Setting up and Development of Byzantine Phema in TaurideThe conditions of the rise and evolution in the structure organs of power of Byzantine thema in Taurica are considered in this article. These problems cannot be solved without realizing the status of Taurica as a part of Byzantine Empire and general foreign policy situation in the Northern Black Sea Coast. By the beginning of the 8th century Byzantium maintained its supremacy over the mountainous and seashore regions of Crimea, the structure of governing them assumes the form of archontia. During the 8th century due to Khazar expension only Cherson and its neighbourhood were under its control. In the beginning of the 9th century due to weakening of Khazaria Byzantium tried to strengthen its influence in this region establishing thema. The evolution of governing had the tendency to increase the rights of stratig, and from the last quarter of the 9th century he became an absolute ruler of the region. The crisis of thema system in Byzantium affected Taurica manifesting itself in rising some themas on its territory and introducing the system of katepanat in the end of the 10th – 11th centuries. Since the end of the 11th century there is no evidence of sources about Byzantine thema in Taurica, that could be connected with its disappearing.